2020
DOI: 10.1186/s12913-020-05846-7
|View full text |Cite
|
Sign up to set email alerts
|

Accessing health services in India: experiences of seasonal migrants returning to Nepal

Abstract: Background Migration to India is a common livelihood strategy for poor people in remote Western Nepal. To date, little research has explored the degree and nature of healthcare access among Nepali migrant workers in India. This study explores the experiences of returnee Nepali migrants with regard to accessing healthcare and the perspectives of stakeholders in the government, support organizations, and health providers working with migrant workers in India. Methods Six focus group discussions (FGDs) and 12 i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Few data are available on the health status of migrant workers in Europe, but previous studies in Nepal, Tanzania and Ethiopia have documented a low prevalence of HIV in migrant farm workers, low condom use, high risk of risky sex and high prevalence of malnutrition, and reinforce the need for screening for diseases related to a poor quality of work and life, which is strongly correlated with tuberculosis and non-communicable diseases, such as hypertension and diabetes, and overwork illnesses, such as rickets, asthenia, muscle/fatigue pain and mental health illnesses [ 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few data are available on the health status of migrant workers in Europe, but previous studies in Nepal, Tanzania and Ethiopia have documented a low prevalence of HIV in migrant farm workers, low condom use, high risk of risky sex and high prevalence of malnutrition, and reinforce the need for screening for diseases related to a poor quality of work and life, which is strongly correlated with tuberculosis and non-communicable diseases, such as hypertension and diabetes, and overwork illnesses, such as rickets, asthenia, muscle/fatigue pain and mental health illnesses [ 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study conducted by Adhikary et al (2020) found that "migration to India continues to be livelihood strategy for Nepali male workers, especially unskilled migrants. The researchers concluded that most migrants had di culty accessing healthcare services in India and low wages, lack of documentation, identity card, the now ubiquitous Aadhar, biometrics, lack of insurance, apathy of employers and discrimination in Indian healthcare facilities were some of the reasons that acted as barriers to healthcare and low healthcare utilization.…”
Section: The Link Between Migration and Hivmentioning
confidence: 99%
“…The researchers concluded that most migrants had di culty accessing healthcare services in India and low wages, lack of documentation, identity card, the now ubiquitous Aadhar, biometrics, lack of insurance, apathy of employers and discrimination in Indian healthcare facilities were some of the reasons that acted as barriers to healthcare and low healthcare utilization. The authors conclude that institutional ties between the two governments have to be strengthened and more migrant support organizations with support for health care and employer accountability must be enhanced (Adhikary et al, 2020).…”
Section: The Link Between Migration and Hivmentioning
confidence: 99%
“…In accordance with the well-recognized global disease burdens, Nepali migrants suffer from several health issues that include but are not limited to heart diseases, renal diseases, mental health issues that lead to suicidal ideation and attempts. 6 , 7 , 8 , 9 Unpublished data from the Middle East show the health seeking behavior is low among Nepali migrants as they tend to be of younger population demographics and they do not visit a doctor or clinic until the health situation is serious.…”
Section: Introductionmentioning
confidence: 99%